Spiritual Leadership in Organizations: Literature Review - Uthami, I Gusti Ayu Agung Dewi Kurnia; Supartha, Gede; Dewi, I Gusti Ayu Manuati; Surya, Ida Bagus (Al Makki Publisher, 2024)
Spiritual leadership has become an increasing focus of attention in organizational research. This systematic review aims to provide a comprehensive overview of spiritual leadership research in an organizational context. This study used the systematic literature review research method. The data collection technique in this study involved exploring journals, books, and other information relevant to the research. The data that has been collected is then analyzed thematically. Based on the analysis results, a person essential in leading an organization is called a leader. A leader cannot move alone; he needs members to achieve organizational goals. Leaders need a way or leadership style to direct and guide members. One leadership style that can be used in leading an organization is spiritual leadership. Spiritual leadership believes that the proper leader is God. The analysis results also show that spiritual leadership is positively related to safety compliance, employee safety participation, and employee innovative behavior, as well as increases workplace spirituality, job satisfaction, and workplace deviant behavior. Thus, spiritual leadership has a positive impact on the organization